Pengaruh Penggunaan E-Wallet terhadap perilaku Manajemen Keuangan Mahasiswa Universitas Pamulang Tangerang Selatan - Leahani Nasyaroyan Imani; Titin Fatimah; Dedeh Septyaningsih; Rudi Sanjaya (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to analyze the effect of e-wallet usage on the financial management behavior of Pamulang University students, South Tangerang. With the increasing development of technology, e-wallets have become one of the payment instruments widely used by the public, especially the younger generation. This study uses a quantitative approach with a survey method by distributing questionnaires to Pamulang University students. The results of the study indicate that there is a significant relationship between e-wallet usage and students' financial management behavior, especially in terms of budget management, recording expenses, and financial discipline. This study provides recommendations for improving financial literacy among students in order to maximize the benefits of using e-wallets.